A review on solubility measurement in supercritical condition - Yeoh, Hooi Sim; Chong, Gun Hean; Mohd Adzahan, Noranizan; Abdul Rahman, Russly; Choong, Thomas Shean Yaw (Faculty of Engineering, Universiti Putra Malaysia, 2012)
Supercritical fluid technology (SFT) has been applied in many areas such as petroleum and coal, environmental, material processing, pharmaceutical and food sectors due to its outstanding features. As global environmental issues are much concerned nowadays, SFT is a clean, sustainable and efficient technology to perform extraction, particle formation, purification and fractionation process while leaving no or less organic residues compared to conventional process. In order to apply SFT in processes, solubility data of interest compound in the supercritical fluid plays an important role. Fundamental knowledge of solubility also contributes in optimizing, designing and scaling up the mentioned processes. Although many researchers had done the solubility study for different compounds, yet there is still lacking of review that summarizes the experimental method used to measure solubility concisely. Therefore, this article is produced to review the solubility measurement method and discuss the advantages and disadvantages of each method as well as precautions needed when dealing with various kinds of method.